A review of the impact of sensory processing sensitivity on mental health in university students - Allison Mac, PharmD, BCPS; Myo-Kyoung Kim, PharmD, EdD, BCPS; Rajkumar J. Sevak, MPharm, PhD, RPh (American Association of Psychiatric Pharmacists, 2024)
Introduction The concept of sensory processing sensitivity (SPS) was first introduced by Aron and Aron (1996) as an innate trait characterized by heightened processing of sensory, emotional, and physical stimuli. Since the concept's introduction in 1996, high SPS has been shown to be associated with poor physical and mental health. It is possible that this is especially true in university students, who are frequently faced with numerous stressors, such as intense workloads and test anxiety. Methods This article is a systematic literature review conducted through EBSCOHost using the following databases: Academic Search Complete, APA PsycArticles, APA PsycInfo, Education Research Complete, ERIC, MEDLINE Complete, and SocINDEX. Search terms included terms regarding high sensory processing sensitivity, university or professional students, and mental health. Results A total of 6 studies were included. University students with high SPS experienced heightened reactions to sensory, emotional, and physical stimuli. The studies demonstrate correlations of high SPS with outcomes such as depressive tendencies and difficulty adjusting to college. Discussion These findings highlight that SPS is associated with poor mental health outcomes. The results underscore the importance of developing support methods for students with high SPS. Future studies should further explore SPS in university students to develop targeted support methods and programs.